2017
DOI: 10.1038/s41598-017-01040-8
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Electrochemical Synthesis of Platinum Black

Abstract: We present electrochemical and chemical synthesis of platinum black at room temperature in aqueous and non-aqueous media. X-ray analysis established the purity and crystalline nature. The electron micrographs indicate that the nanostructures consist of platinum crystals that interconnect to form porous assemblies. Additionally, the electron micrographs of the platinum black thin layer, which was electrochemically deposited on different metallic and semiconductive substrates (aluminium, platinum, silver, gold, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…It was demonstrated that platinum black can be electroc–hemically synthesized in non-aqueous media 16 . On this basis, a sub-visible-wavelength thick layer of platinum black in isopropanol is electrochemically constructed (§Methods).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was demonstrated that platinum black can be electroc–hemically synthesized in non-aqueous media 16 . On this basis, a sub-visible-wavelength thick layer of platinum black in isopropanol is electrochemically constructed (§Methods).…”
Section: Discussionmentioning
confidence: 99%
“…Electrolysis times varying from 30 s to 300 s have been examined, and it was found that 90 s represents the optimum one for compact layers of 100 nm thickness. In aqueous media the electro-assembling of platinum black on cathodes of different materials is prepared as described in our previous work 16 . Electrolytic bath: 0.05 g PtCl 4 and 0.008 g Pb(CH 3 COO) 2 dissolved in 10 mL water.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Platinum black deposition solution was prepared by mixing 1% chloroplatinic acid and 0.05% lead acetate in DI water. The mixture was then stirred and 0.0025% of 32% hydrochloric acid was added to the mixture (Stanca et al 2017). The prepared solution was covered with aluminum foil and stored at room temperature.…”
Section: Preparing Platinum Black Deposition Solutionmentioning
confidence: 99%